DIAGNOSTIC VALUE OF MARKERS OF ENDOTHELIUM VESSELS INJURY IN DIABETES TYPE 2 WITH ARTERIAL HYPERTENSION - N. E. Tadtaeva; O. O. Basieva (Кубанский научный медицинский вестник)
The purpose of the investigation is to study the breach of functional endothelial activity of the patients with type 2 diabetes (DM2) with arterial hypertension. In investigation includes 56 patients (middle age 53,34±0,99). The control group consists of 20 clinical healthy people (middle age 55,1±1,67). The results show that patients with DM2 and arterial hypertension are characterized by reliable increase of circulating endothelial cells and the reduction of basal secretion of NO by endothelium. The listed changes are intensified in depended of the duration of DM2.